Struktur dan Ciri-Ciri Teks Argumentasi dalam Bahasa Indonesia: Analisism dan Contoh - Anissa Dwi Utami; Miftahul Fadlilah; Nadya Quratul Aini; Rahmi Aulia Syafutri (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This article discusses the structure and characteristics of argumentative texts in Indonesian. Argumentative text is a type of text that is used to express opinions or arguments about a topic, and has a specific structure. In this article, we will analyze the structure and characteristics of argumentative texts in Indonesian, as well as provide relevant examples. Argumentative texts in Indonesian have a structure consisting of several parts, namely: introduction, body and conclusion. The introduction functions as an introduction, while the body contains the arguments put forward. The conclusion functions as confirmation and closure. The characteristics of argumentative texts in Indonesian include: using clear and short sentences, using examples and relevant data, and using clear and logical logic. Argumentative texts must also have a clear and logical structure, so that readers can follow the arguments put forward. In this article, we will also discuss relevant examples of argumentative texts in Indonesian. These examples will help us understand the structure and characteristics of argumentative texts more clearly. In conclusion, this article hopes to help readers understand the structure and characteristics of argumentative texts in Indonesian, as well as providing relevant examples. By understanding the structure and characteristics of argumentative texts, we can create argumentative texts that are more effective and easier to understand.